Pengaruh Profesionalisme Dan Motivasi Kerja Terhadap Efektivitas Pelayanan Kesehatan Masyarakat Pada Badan Layanan Umum Daerah (BLUD) Rumah Sakit Kabupaten Tulang Bawang - MALIK Malik (e-JKPP, 2015)
Professionalism Influence And Motivate The Job of To Effectiveness of Service of Society Health of Public Service Body of Area of Hospital of Regency Tulang Bawang. Problem of this research is : (1) Whether Professionalism have an effect on to Effectiveness of Service of Society Health of Public Service Body of Area of Hospital of Regency Tulang Bawang, (2) Whether Motivation Work to have an effect on to Effectiveness of Service of Society Health of Public Service Body of Area of Hospital of Regency Tulang Bawang, (3) Whether Professionalism and Motivate the Job have an effect on to Effectiveness of Service of Society Health of Public Service Body of Area of Hospital of Regency Tulang Bawang.Research Method used in this research is survey the. Research population as much60 officer people of Public Service Body of Area of Regency Tulang Bawang. While sampel that is as much 60 total or sampel people. Research variable is Professionalism ( X1) and motivate the job ( X2) as free variable and also service effectiveness is variable trussed Y Pursuant to research result indicate that there is good Influence signifikan of professionalism and also motivate the job to service effectiveness of Public Service Body of Area of Hospital of Regency Tulang Bawang. Pursuant to data processing result, that contribution of professionalism variable and motivate the job to service effectiveness, be at the category enough but not yet optimal. The mentioned happened by because not yet the existence of regulation applying in an optimal fashion, so that officer not yet felt there is coherent dubious to officer which impinge the officer order applied At Public Service Body of Area of Hospital of Regency Tulang Bawang.